Comparative risk of end-stage renal disease, myocardial infarction and stroke in young and older onset diabetes in UK Biobank - Kar, Debasish; Molokhia, Mariam; Wierzbicki, Anthony; Koziell, Ania; Byng, Richard; Spicer, Stuart; Farina, Nicolas; Pinkney, Jonathan; Song, Soon; Zabeen, Bedowra; Kar, Shubharthi; Jonnagaddala, Jitendra; et al. (Scientific reports, 2025)
In recent years, coinciding with the increasing incidence of type 2 diabetes mellitus (T2DM) in children and adolescents, the global prevalence of diabetic kidney disease (DKD) and end-stage renal disease (ESRD) are rising year on year. In contrast, the mortality and morbidity due to cardiovascular disease (CVD) and stroke in people with diabetes have been declining. The precise cause of the disparate vascular outcomes in diabetes remains unexplored. To elucidate the relationship, we conducted a retrospective cohort study on the UK Biobank data. In our study, the exposure variables were the age of diabetes and hypertension diagnosis, while the outcome variables were ESRD, myocardial infarction, angina, and stroke. Univariable and multivariable logistic regression models were fitted to assess odds ratios (ORs) and 95% confidence intervals (CIs). Model performance was evaluated using the receiver operating characteristic (ROC) curve. Sensitivity analyses were conducted on participants who developed diabetes before and after the age of 20 years and with and without female participants. Univariable logistic regression showed that compared to those diagnosed after the age of 60, the odds of ESRD for those diagnosed at ages < 20, 20–40, and 41–60 years were 5.26 (3.00 – 9.40), 7.78 (4.81 – 13.16) and 2.33 (1.50 – 3.84), respectively. Myocardial infarction and stroke did not have a statistically significant relationship with younger age of diabetes diagnosis. In those with a dual diagnosis of diabetes and hypertension, irrespective of the age of diabetes diagnosis, the age of hypertension diagnosis at age < 20, 20–40, and 41–60 years, compared to those who developed it after the age of 60 years, had a greater risk of ESRD, 2.20 (1.58 – 3.11), 5.03 (3.79 – 6.81), and 1.53 (1.16 – 2.06), respectively. After adjusting for sex and albuminuria, multivariable logistic regression model 1 showed that compared to those who developed diabetes above the age of 60, those who developed it < 20, 20–40 and 41–60 had a higher risk of ESRD, 4.71 (2.47 – 9.28), 4.67 (2.63 – 8.78), and 1.94 (1.16 – 3.49), respectively. Likewise, in model 2, when the duration of diabetes was used as the explanatory variable, each year of increased duration of diabetes increased the odds of ESRD by 2%, with an odds ratio of 1.02 (1.01–1.03). Younger onset of hypertension but not diabetes increased the odds of myocardial infarction (MI). There was no statistically significant relationship between the age of diabetes, and hypertension diagnoses with angina and stroke. Model performance was excellent, with over 80% of the data points falling below the area under the curve. Sensitivity analyses showed young-onset diabetes as a significant determinant of ESRD. Young-onset and longer-duration of diabetes increase the risk of ESRD. For those with diabetes and hypertension, a younger onset of hypertension but not diabetes may also increase the risk of MI.